Reorientasi Nilai-nilai Kepemimpinan Lembaga Pendidikan Islam Muhammadiyah di Indonesia - Sadari Sadari; Robiatul Adawiyyah; Nurhidayat Nurhidayat; Ummah Karimah (Tamaddun, 2019)
Muhammadiyah is a community organization engaged in education and is popular in Indonesia. Muhammadiyah has been successful in the local-Javanese scope, as well as at the national level. Muhammadiyah educational institutions spread throughout the territory of Indonesia. But as it went on it turned out to have an impact on the emergence of two texture models of Muhammadiyah educational institutions related to leadership, namely the effective model and what it is. The first model, the institution is supported by a strong leadership style, while the second is the opposite. The article further analyzes how these two distinctions can emerge and what steps are important to prepare with the initial assumption that reliance on the "figure" pattern of leadership alone is relatively insufficient. Muhammadiyah managed to manage its educational institutions anchored in the figures' figures. However, as technology, information, the internet and social media develop, there is a shift in orientation patterns. Talking about Muhammadiyah means being oriented towards progress, civilization, new discoveries, for that Muhammadiyah must be more careful, so there is no counter-productive that is contrary to its initial spirit. Based on the case of the distinction between the leadership of educational institutions between what is effective and what it is, this article explains how that can happen, what factors cover, and what actions are important to immediately prepare Muhammadiyah so that it can survive amid the onslaught of both globalization or even the Indonesian people who increasingly technological literacy.